2015
DOI: 10.3329/jesnr.v7i1.22168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microclimatic Parameter on Tea Leaf Production in Different Tea Estates, Bangladesh

Abstract: Abstract:The tea industry of Bangladesh is one of the most important foreign exchange earner and source of income. Sylhet, the northeastern divisional city of Bangladesh, is the major tea-producing region of the country. For this reason the study area was selected in Sylhet district to assess the pattern and causes of fluctuation on tea leaf production in selected tea Estates and the impact of micro-climate change on the productivity of tea leaf. The yield of tea is greatly influenced by microclimatic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…It is advisable to avoid flatter and steeper slopes for tea, as steeper slopes pose a significant risk of soil erosion and landslide, whereas flatlands increase water-logging conditions, which are undesirable for tea production [19]. Aspects have a strong influence on solar radiation and temperature and impact the distribution of tea [17,20]. Variations in these topographic covariates pose ecological stress and limitations as well as opportunities for tea production.…”
Section: Introductionmentioning
confidence: 99%
“…It is advisable to avoid flatter and steeper slopes for tea, as steeper slopes pose a significant risk of soil erosion and landslide, whereas flatlands increase water-logging conditions, which are undesirable for tea production [19]. Aspects have a strong influence on solar radiation and temperature and impact the distribution of tea [17,20]. Variations in these topographic covariates pose ecological stress and limitations as well as opportunities for tea production.…”
Section: Introductionmentioning
confidence: 99%
“…The expected average annual rainfall for the excellent tea leaf production in Bangladesh was 4000-4600 mm (Ali et al, 2014). Ochieng et al (2016) revealed that a consistent rainfall pattern is the determinant of high productivity, and any signi cant deviation affects the production.…”
Section: Relationship Between Rainfall and Yieldmentioning
confidence: 99%
“…The various study showed that the drought alters the metabolites' concentration (Ahmed et al, 2014;Cai et al, 2013;Eric et al, 2019;Kfoury et al, 2018;Han et al 2017). Few studies measured the rainfall's impact on the tea yield of a single or few tea gardens of the Sylhet district (Islam et al, 2021;Rahman et al, 2017;Ali et al, 2014). A study including all tea-producing areas will help better understand the change in rainfall distribution area-wise and the effect on tea yield and the quality of the products.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of tea pathogens are, thus, not surprising for their existence in tea monoculture across diverse topography, climate, planting material and cultural practices and thereby leads to pathogenesis in tea. According to Lehmann-Danzinger (2000); Anita et al (2012) and Ali et al (2014) tea naturally encourage for the establishment of several tea pathogens as it mostly favours a stable microclimate with alternating wet and dry periods. Blister blight (Exobasidium vexans), black rot (Corticium invisum and C. theae), red rust (Cephaleuros parasiticus and C. mycoidea), charcoal stump rot (Ustulina zonata), brown root rot (Fomes lamaeonsis), black root rot (Rosellina arcuata), Fusarium die back (Fusarium solani), brown blight (Colletotrichum sp.…”
Section: Introductionmentioning
confidence: 99%